Penyelesaian Sengketa Kepailitan Ekonomi Syariah Perspektif Ibnu Rusyd Al-Qurthubi Dalam Bidayatul Mujtahid Wa Nihayatul Muqtashid - Muhamad Subhi Apriantoro; Salsabilla Ines Sekartaji; Apriliya Suryaningsih (Jurnal Ilmiah Ekonomi Islam, 2021)
The study discusses the settlement of sharia economic bankruptcy disputes from the perspective of Ibn Rushd Al-Qurtubi. As someone who had a career in the world of Islamic courts in his day, Ibn Rushd had many reflective records of the disputed cases he handled. The phenomenon of resolving bankruptcy disputes experienced by Ibn Rushd at that time was also experienced by most Muslims today, especially seeing that many companies went bankrupt due to the pandemic, so that Ibn Rushd's character, especially ijtihad in resolving bankruptcy disputes, needs to be the primary basis of this research. This study is pure library research and the material used as the primary data source is the book Bidayatul Mujtahid wa Nihayatul Muqtashid. From the results of the research, it is known that even though Ibn Rushd is a Maliki school of thought, in some cases, he puts forward objectivity by using analytic tools to conclude a legal product, even though in settlement of bankruptcy disputes, he is more dominantly inclined to strengthening the Maliki school. Bankruptcy dispute cases that existed in the era of Ibn Rushd, although using a simple transaction background, can be analogous to cases of dispute resolution at this time by prioritizing the similarity of illat (rational reasons), which combines two different cases so that the development of fiqh law goes well without the presence of rigidity.